2006
DOI: 10.3892/or.15.1.275
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative effect of horehound leaf and wild cherry bark extracts on human colorectal cancer cells

Abstract: Marubium vulgare (horehound) and Prunus serotina (wild cherry) have been traditionally used for the treatment of inflammatory-related symptoms such as cold, fever, and sore throat. In this report, we show that extracts of anti-inflammatory horehound leaves and wild cherry bark exhibit antiproliferative activity in human colorectal cancer cells. Both horehound and wild cherry extracts cause suppression of cell growth as well as induction of apoptosis. We found that horehound extract upregulates pro-apoptotic no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
19
0
3
Order By: Relevance
“…Our findings provided insight into a new implication of the traditional usage of M. persicum found in Armenia, Azarbaijan, Turkey and Iran as a potential novel cancer chemopreventive agent, where incorporation of this plant in herbal remedy may help prevent or reduce the risk of breast cancer and other oxidative stress associated diseases. Several studies in this filed have shown that genus Marrubium is of potential value for detecting antiproliferative agents, as Yamaguchi et al determined the anti-inflammatory and antiproliferative activity of M. vulgare leaves in human colorectal cancer cells via suppression of cell growth as well as induction of apoptosis (Yamaguchi et al, 2006). Elsewhere, diterpenoids from M. cylleneum and M. velutinum were evaluated for their cytotoxic effects against various cancer cell line and immunomodulating potential in human peripheral blood mononuclear cells in vitro assays by Karioti et al, revealing strong tumor regression in a broad range of tumor cells (Karioti et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings provided insight into a new implication of the traditional usage of M. persicum found in Armenia, Azarbaijan, Turkey and Iran as a potential novel cancer chemopreventive agent, where incorporation of this plant in herbal remedy may help prevent or reduce the risk of breast cancer and other oxidative stress associated diseases. Several studies in this filed have shown that genus Marrubium is of potential value for detecting antiproliferative agents, as Yamaguchi et al determined the anti-inflammatory and antiproliferative activity of M. vulgare leaves in human colorectal cancer cells via suppression of cell growth as well as induction of apoptosis (Yamaguchi et al, 2006). Elsewhere, diterpenoids from M. cylleneum and M. velutinum were evaluated for their cytotoxic effects against various cancer cell line and immunomodulating potential in human peripheral blood mononuclear cells in vitro assays by Karioti et al, revealing strong tumor regression in a broad range of tumor cells (Karioti et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…NAG-1 is up-regulated by a number of anti-tumorigenic compounds in addition to NSAIDs, including peroxisome proliferator-activated receptor γ (PPARγ) ligands (Baek et al, 2003;2004b;Yamaguchi et al, 2006a), phosphatidylinositol 3-kinase inhibitor (Yamaguchi et al, 2004) and chemopreventive dietary compounds, such as resveratrol (Baek et al, 2002a), indole-3-carbinol , conjugated linoleic acid (Lee et al, 2006) and epicatechin gallate (Baek et al, 2004a), as well as anti-inflammatory plant extracts (Yamaguchi et al, 2006b). Interestingly, induction of NAG-1 by these compounds occurs by multiple mechanisms at the levels of transcription and post-transcription.…”
Section: Introductionmentioning
confidence: 99%
“…However, NAG-1 has been shown to possess antitumorigenic and proapoptotic activity in some types of cancer cells (19,22,23). NAG-1 is up-regulated in several epithelial cancer cell lines by several nonsteroidal anti-inflammatory drugs (23), as well as by antitumorigenic compounds such as resveratrol (24), catechins (25), indole-3 carbinol (26), conjugated linoleic acid (27), PPARg ligands (13), DIM derivatives (28), horehound extracts (29), and 5F-203 (30). In contrast to other transforming growth factor-h superfamily genes, NAG-1 contains a p53 binding site in the 5 ¶ upstream region (19,22,23), and several dietary compounds induce NAG-1 expression via p53 (24,25).…”
Section: Introductionmentioning
confidence: 99%